2022
DOI: 10.1155/2022/1649605
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Electroacupuncture Promotes Angiogenesis after Stroke in Rats by Activation of Wnt/β-Catenin Signal Pathway

Abstract: Background. Scalp acupuncture is a contemporary acupuncture method based on the fundamental theories of traditional acupuncture, which has been widely used in patients with stroke in China. However, the effectiveness is controversial due to lack of solid experimental evidence. Methods. In this study, a rat model of cerebral ischemia-reperfusion injury (CIRI) was established by the middle cerebral artery occlusion/recirculation. The efficacy of scalp acupuncture against CIRI was evaluated by the mNSS scores, TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Sha et al [ 28 ] believe that acupuncture can relieve neuronal inflammation by inhibiting miR-223/NLRP3 pathway, thus playing a protective role for nerves. Shi et al [ 29 ] reported that acupuncture was able to activate the Wnt/β-catenin signaling pathway and up-regulate angiogenesis factor expression, thereby promoting angiogenesis after cerebral infarction. In promoting neural tissue remodeling, studies have shown that [ 30 , 31 ] acupuncture can activate nerve growth factors and promote the proliferation of neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sha et al [ 28 ] believe that acupuncture can relieve neuronal inflammation by inhibiting miR-223/NLRP3 pathway, thus playing a protective role for nerves. Shi et al [ 29 ] reported that acupuncture was able to activate the Wnt/β-catenin signaling pathway and up-regulate angiogenesis factor expression, thereby promoting angiogenesis after cerebral infarction. In promoting neural tissue remodeling, studies have shown that [ 30 , 31 ] acupuncture can activate nerve growth factors and promote the proliferation of neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“… 186 In addition, applying EA at GV20 can activate the expression of VEGF mediated by Wnt/β-catenin signaling pathway, thereby promoting angiogenesis and restoring blood perfusion in ischemic areas. 187 The miR-210 extracted from the serum of diseased mice treated with EA (EA-EXO) can increase the levels of HIF-1α, VEGF, and Notch1 proteins in rats with cerebral ischemia and promote angiogenesis. 188 …”
Section: Angiogenesismentioning
confidence: 99%
“…Studies show electroacupuncture increases EPC quantity and accelerates EC growth. 58 Moreover, acupuncture may stimulate angiogenesis via Vascular Endothelial Growth Factor (VEGF), 59 EphB4/EphrinB2, 60 SDF-1α/CXCR4, 58 and Apelin/APJ pathways. 61…”
Section: Ischemic Strokementioning
confidence: 99%